Identification and functional characterization of a novel splicing variant in the F8 coagulation gene causing severe hemophilia A. (29th April 2020) - Famà, Rosella; Borroni, Ester; Zanolini, Diego; Merlin, Simone; Bruscaggin, Valentina; Walker, Gillian E.; Olgasi, Cristina; Babu, Deepak; Agnelli Giacchello, Jacopo; Valeri, Federica; Giordano, Mara; Borchiellini, Alessandra; et al.
Abstract: Background: We have identified a synonymous F8 variation in a severe hemophilia A (HA) patient who developed inhibitors following factor VIII (FVIII) prophylaxis. The unreported c.6273 G > A variant targets the consensus splicing site of exon 21. Objectives: To determine the impact of c.6273 G > A nucleotide substitution on F8 splicing and its translated protein. Methods: Patient peripheral blood mononuclear cells were isolated and differentiated into monocyte‐derived macrophages (MDMs). FVIII distribution in cell compartments was evaluated by immunofluorescence. The splicing of mutated exon 21 was assessed by exon trapping. Identified FVIII splicing variants were generated by site‐directed mutagenesis, inserted into a lentiviral vector (LV) to transduce Chinese hamster ovary (CHO) cells, and inject into B6/129 HA‐mice. FVIII activity was assessed by activated partial thromboplastin time, whereas anti‐FVIII antibodies and FVIII antigen, by ELISA. Results: HA‐MDMs demonstrated a predominant retention of FVIII around the endoplasmic reticulum. Exon trapping revealed the production of two isoforms: one retaining part of intron 21 and the other skipping exon 21. These variants, predicted to truncate FVIII in the C1 domain, were detected in the patient. CHO cells transduced with the two FVIII transcripts confirmed protein retention and absence of the C2 domain. HA mice injected with LV carrying FVIII mutants, partially recovered FVIII activity without the appearance of anti‐FVIII antibodies. Conclusions: Herein, we demonstrate the aberrant impact of a FVIII synonymous mutation on its transcription, activity, and pathological outcomes. Our data underline the importance of increasing the knowledge regarding the functional consequences of F8 mutations and their link to inhibitor development and an effective replacement therapy.